A Novel Dual-Shorting Point PIFA (GSM850 to IMT-A) for Mobile Handsets - Pengcheng Li; Jin Pan; Deqiang Yang; Pingzai Nie (International Journal of Antennas and Propagation)
A novel planar inverted-F antenna (PIFA) with dual-shorting points is proposed for multiband mobile handsets. The antenna comprises a meandered strip, a feeding point, two shorting points, and a slotted ground plane. For bandwidth enhancement of DCS/PCS/UMTS/WLAN 11.b/LTE2300/2500 and IMT-Advanced (International Mobile Telecommunications-Advanced), the antenna applies a dual-shorting points design, which generates a multimode between 1707 and 2815 MHz. The proposed antenna has good impedance matching characteristics for GSM (824–960 MHz)/DCS (1710–1880 MHz)/PCS (1850–1990 MHz)/UMTS (1920–2170 MHz)/LTE (2300–2400 MHz, 2500–2690 MHz)/WLAN 11.b (2400–2480 MHz) and IMT-A (4200–4800 MHz). The measured radiation efficiencies of the proposed antenna were all higher than 60% in GSM850/900, DCS/PCS, UMTS, LTE2300/2500, and WLAN 802.11 b, and it is up to 86% in IMT-A.